Study and simulation of PV Emulator based on DC-DC Push-Pull Converter - TOUHAMI, Oussama; BENMEHIRIS, Makhlouf; Hadj Aissa, Aboubakeur (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
The aim of this master project is to model and study about the photovoltaic emulator (PVE), the letter is based on DC-DC push-pull converter controlled by PI controller. The PVE is designed in order to simulate the behaviour of photovoltaic panels. To achieve the objective of this master’s project, we started by studying and modeling of the PV panel by its equivalent electrical circuit, then modeling and analysis of the push-pull converter through the state space representation then the average model calculation in order to define the PI parameters through frequency analysis (Bode diagram). The founded results show the effectiveness of our proposed PVE structure
SPECIALTY: Instrumentation